The Optical and Vesta Projects: Ophthalmic Visualization and Virtual Surgery - Barsky, Brian A.; Downes, Michael S.; Tendick, Frank (International Journal of Virtual Reality, 2001)
In this paper we describe two projects. The first is our novel and superior method of calculating the shape of the cornea of the eye from measuring instuments, called videokeratographs, that typically shine a pattern (usually rings) of light onto the cornea and then capture the reflection pattern on a CCD array using a built-in video camera. Accurate and detailed information about the shape of the cornea is critical for the diagnosis and correction of vision problems. The second project is a virtual environment simulation of the surgical procedure of minimallyinvasive gallbladder removal, which is known as laparoscopic cholecystectomy. Our simulation is designed to enable us to easily experiment with different approaches to addressing the major issues of surgical simulation, and it represents our attempt to leverage a great deal of surgical experience in creating a simulation that focuses on the most important, most error-prone steps in the procedure. Currently we are expanding the simulation code to serve as a general-purpose surgical simulation authoring tool, experimenting with new tissue modeling techniques, and constructing a new haptic interface device.